The reduction of tap water consumption through the use of grey water installations in a collective residence building – economic analysis - Badowska, Ewa; Bandzierz, Dawid; Pizia, Julitta (Instal, 2023)
There are two main ways to reduce the consumption of tap water in buildings, usage of gray sewage or rainwater, for part of the needs of the building and its users. This publication presents an analysis of the possibilities for using a gray sewage collection and pre-treatment system in a collective housing building – a dormitory inhabited by 195 people. The main goal of the modernization presented in the publication was to design adual water and sewage installation in the existing building, which supplements the existing installation with sewage risers collecting water from washbasins and showers, and a water supply installation supplying gray water to the flush toilets and urinals in the collective residence building – Student Dormitory No. 1 located at Alei Politechniki 3b in Łódź, along with preparing a cost estimate of the installation. The analysis was based on the actual consumption of tap water in the Student Dormitory, and the costs of using the facility were analyzed in relation to fees for tap water and sewage, as well as the costs of electricity.